Assessment of Foods and Drinks for the Presence of Extended Spectrum Beta Lactamase (ESBL) Producing Bacteria in Gombe Metropolis, Nigeria - Shu’aibu, I.; Hadiza, J. A.; Yusha’u, M.; Kabiru, M. Y.; Ahmad, Mani Malam; Lawal, G.; Adamu, M. T.; Khairiyya, M. (Informatics Publishing Limited, 2016)
Objectives: To make preliminary screening study for the presence of ESBL producing bacteria, in food and drinks sold in Gombe metropolis. 30 samples of food and drinks were collected and analyzed. Method: Bacterial isolation was performed on nutrient agar and identification started from gram staining; the gram negative isolates obtained, among which ESBL producers were found and further subjected to standard biochemical tests and confirmed to be enterobacteriaceae. They were then screened for ESBLs in accordance with Clinical and Laboratory Standard Institute (CLSI) breakpoint, and the suspected ESBLs bacteria were confirmed using double disc synergy testing (DDST) with standard Augmentin (Amoxycillin/ Clavulanic Acid, 30μg; Oxoid England, CT0223B), Ceftriaxone (CRO 30μg; Oxoid England, CT0417B) and Ceftazidime (CAZ 30μg; Oxoid England, CT0412B). Findings: The fourteen 14(100%) Gram negative bacteria isolated were found to include Pseudomonasaeruginosa 2(14.29%) and members of the family Enterobacteriaceae (enteric gram negative rods): Citrobacterfreundii 2(14.29%), Enterobacterspp. 1(7.14%), Escherichiacoli 4(28.57%), Klebsiellapneumoniae 3(21.43%), Proteusvulgaris 1(7.14%) and Salmonellatyphi 1(7.14%). When screened for ESBL production based on CLSI breakpoint, only 6 (49.99%) were positive and included C.freundii 1(7.14%), E.coli 2(14.29%), K.pneumoniae 1(7.14%), S. typhi 1(7.14%) and 1(7.14%) for Ps. aeruginosa. On subjecting them to DDST, only 2(33.34%) out of them were found to be ESBLs positive by an increase in inhibition zone of 5mm toward the centre disc, Augmentin. They include E. coli 1(16.67%) and S. typhi 1(16.67%). Application: In a nutshell, foods and drinks sold therein could serve as reservoirs for ESBLs producing bacteria.